Mutations in the postsynaptic density signaling hub TNIK disrupt PSD signaling in human models of neurodevelopmental disorders - Jiang, Jianzhi; Wilkinson, Brent; Flores, Ilse; Hartel, Nicolas; Mihaylov, Simeon R.; Clementel, Veronica A.; Flynn, Helen R.; Alkuraya, Fowsan S.; Ultanir, Sila; Graham, Nicholas A.; Coba, Marcelo P. (Frontiers in Molecular Neuroscience, 2024)
A large number of synaptic proteins have been recurrently associated to complex brain disorders. One of these proteins, the Traf and Nck interacting Kinase (TNIK) is a post synaptic density (PSD) signaling hub, with many variants reported in neurodevelopmental disorders (NDD) and psychiatric disease. While rodent models of Tnik dysfunction have abnormal spontaneous synaptic activity and cognitive impairment, the role of mutations found in patients with TNIK protein deficiency and TNIK protein kinase activity during early stages of neuronal and synapse development have not been characterized. Here, using hiPSC derived excitatory neurons, we show that TNIK mutations dysregulate neuronal activity in human immature synapses. Moreover, the lack of TINK protein kinase activity impairs MAPK signaling and protein phosphorylation in structural components of the PSD.We show that the TNIK interactome is enriched in NDD risk factors and TNIK lack of function disrupts signaling networks and protein interactors associated to NDD that only partially overlap to mature mouse synapses, suggesting a differential role of TNIK in immature synapsis in NDD.